Environmental management of human resources and level of employees' engagement in organizations - Camargo, Jose Alberto [UNESP]; Liboni, Lara Bartocci; De Oliveira, Jorge Henrique Caldeira [UNESP] (FapUNIFESP (SciELO), 2015)
The aim of this article is to suggest indicators to make a connection between the engagement of employees and the management of environmental projects undertaken in organizations. The indicators developed are intended to measure the level of commitment of employees to the organizations when they promote projects related to environmental management. It is, therefore, a theoretical and empirical study. In the future, such indicators may propose a scale that helps to understand the effectiveness of these environmental projects by engaging employees in the organization, from its planning to its implementation and results. It is hoped that the contributions are useful for researchers so they can propose new studies that can improve the indicators hereby presented, and that they allow other studies to apply these indicators in public or private organizations.
Gestão ambiental de recursos humanos e nível de envolvimento de colaboradores nas organizações
Keywords: Employees; Environmental Project Management; Green HRM; Indicators; Sustainability